All‐Dielectric Metamaterial Fabrication Techniques. Issue 1 (20th November 2020) - Bi, Ke; Wang, Qingmin; Xu, Jianchun; Chen, Lihao; Lan, Chuwen; Lei, Ming
Abstract: All‐dielectric metamaterials with low loss are a rapidly developing research hotspot in the field of metamaterials, and offer additional design freedom for electromagnetic devices. Many types of fabrication techniques are used to prepare all‐dielectric metamaterials, so as to realize specific physical properties. A key to efficient electromagnetic manipulation is the proper choice of the fabrication technique, which enables the all‐dielectric metamaterials to be easily coupled to integrated devices. Here, an overview of existing fabrication techniques for all‐dielectric metamaterials is provided. Based on material compositions and accuracy requirements, typical fabrication methods for microwave, terahertz, and optical all‐dielectric metamaterials are discussed. In addition, the advantages and disadvantages of each fabrication method are outlined. This comparative analysis of all‐dielectric metamaterial fabrication techniques will be valuable for the design of novel all‐dielectric metamaterials with desired physical properties, thereby expanding the scope of their applications. Abstract : Proper fabrication technique is the key factor for realization of all‐dielectric metamaterials, which can be easily coupled to integrated devices. This review introduces the existing fabrication technologies of microwave, terahertz, and optical all‐dielectric metamaterials. Their advantages and disadvantages are also outlined, which is beneficial for the design of novel all‐dielectric metamaterials.